Determination of Human Population Kinship in Kei Islands Genetically using Mitochondrial DNA Marker - Feby Ramadhani (NIM : 10613033), Fania
The southern Moluccan islands comprise of islands with different languages and cultures, one of which is the Kei Islands. Although located in eastern Indonesia that is generally populated by ethnic Papuans, but in terms of language the Kei population using the Austronesian language. In this study aims to determine the kinship of human population in the Kei Islands genetically using mitochondrial DNA markers. Mitochondrial DNA, especially in the Hypervariable Region (HVR) can be used as a genetic marker because it has polymorphisms that is useful for grouping in haplogroup. There are 33 samples in total for this study and came from three villages of Kei Island, namely Ohoidertutu, Faan, and Waur. Total DNA isolation was done from peripheral blood samples, then HVR 1 and 2 areas in mtDNA were amplified with PCR and sequenced. Haplogrup checking was done using Mitomaster software to determine the haplogroup. Next step is the determination of genetic difference values (FST) between villages in the population using Arlequin software and making MDS plot with SPSS. From 33 samples in total, 7 belongs to B4 haplogroup, 7 B5 haplogroup, 4 E1 haplogroup, 4 R9 haplogroup, and 11 belong to others. FST values between villages were 0.09085 for Ohoidertutu and Faan respectively, 0.09371 for Ohoidertutu and Waur villages, and 0.03534 for Faan and Waur villages. Based on the Mann-Whitney test, the mean FST between Kei and populations in western and eastern Indonesia has statistically significant differences. After the MDS analysis, it turns out that the Kei population is closest to the Papuan population. The conclusion of this experiment is that genetically, the human population of Kei has the closest relationship to the human population of Papua compared to other islands in Indonesia.